Common hardships while speaking in target language and the ways to get rid of them - Abdurazokov, Ulugbek (Журнал иностранных языков и лингвистики, 2021)
In this day and age, the honor of different international languages, such as English, Spanish, and Chinese and so on, is increasing considerably all over the world. It is not only due to their spectacular interactive feature among nations, but they are becoming the only keyto build the most successful commercial agreements among gigantic countries. It is given, at the same time the great attention is paying to educating this perfect communicating tool in our developing country. At virtually all stage of education, teaching at least one foreign language is one of the important refreshments of our educational system recently. Indeed, last three year has been considered a big turning point of our studying procedure that is characterized several significant laws and presidential decisions have been made. As a response to these newly created opportunities, it is required to us to present ourselves not only local areas butat international arenas by showing our great history and powerful ancestors.